Evaluation of hypoxia-inducible factor-1α and urine non-transferrin-bound iron concentrations in cats with chronic kidney disease - Chien-Hui Chen; Chien-Hui Chen; Wei-Li Hsu; Pei-Shiue Jason Tsai; Chun-Fu Lai; Meng-Ting Wu; Ya-Jane Lee; Ya-Jane Lee (Frontiers in Veterinary Science)
IntroductionHypoxia-inducible factors (HIF) regulate gene transcription, which aids hypoxia adaptation while promoting renal fibrosis. Non-transferrin-bound iron (NTBI) is a catalytic form of iron that can lead to oxidative damage. However, NTBI in cat biofluids has rarely been evaluated.AimsWe assessed cat plasma and urine HIF-1α (pHIF-1α/uHIF-1α) concentrations and urine NTBI (uNTBI) concentrations to investigate their relationship with chronic kidney disease (CKD) severity.MethodspHIF-1α and uHIF-1α concentrations were measured using commercial ELISA kits, while uNTBI concentrations were detected by inductively coupled plasma mass spectrometry.ResultsHealthy cats (n = 35) and cats with CKD (n = 84) formed the study cohorts. pHIF-1α concentrations increased from 9.48 pg./mL (median) in the healthy cohort to 11.42 pg./mL in early-stage CKD cats but decreased to 8.50 pg./mL in late-stage CKD cats. uHIF-1α concentrations gradually decreased with a significant difference between the control group (44.61 pg./mL) and the late-stage CKD group (36.79 pg./mL, p < 0.001). Cats with proteinuria had significantly higher uNTBI concentrations (35.61 ppb) than non-proteinuric cats (25.13 ppb, p = 0.019). Finally, the concentrations of pHIF-1α and uHIF-1α were positively correlated independent of renal function.Conclusion and clinical importanceOverall, pHIF-1α and uHIF-1α concentrations are lower in advanced CKD cats, while uNTBI concentrations are significantly higher in proteinuric cats.